2007
DOI: 10.1111/j.1600-051x.2007.001069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three different dental health preventive programmes on young adult individuals: a randomized, blinded, parallel group, controlled evaluation of oral hygiene behaviour on plaque and gingivitis

Abstract: The study confirms the efficacy of three different preventive programmes in reducing supragingival plaque and gingival inflammation. Professional tooth cleaning provided no clinical benefit beyond that derived from individual and group-based health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 20 publications
3
67
0
7
Order By: Relevance
“…These studies were carried out using both child and adult subjects (see Table 5). [7][8][9][10]33 For example, while four of these studies [7][8][9][10] found that frequent dental prophylaxis and comprehensive OHI resulted in a reduction of gingivitis, none was able to demonstrate elimination of gingivitis, which was their stated…”
Section: Gingival Healthmentioning
confidence: 99%
“…These studies were carried out using both child and adult subjects (see Table 5). [7][8][9][10]33 For example, while four of these studies [7][8][9][10] found that frequent dental prophylaxis and comprehensive OHI resulted in a reduction of gingivitis, none was able to demonstrate elimination of gingivitis, which was their stated…”
Section: Gingival Healthmentioning
confidence: 99%
“…Our main addition to the literature is that similar to areas in medicine, [2830] dental SPVSs were able to be used easily and efficiently to record, monitor, and evaluate change over time in TB skills after a brief intervention. Importantly, our measure of TB behavior was directly observed and not based on plaque accumulation, gingival or periodontal health; [3133] such direct observation is critical component to implement and evaluate future IMB-based or informed interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the promising results [9], most studies that used the MI technique in dentistry and in patients with periodontal problems was developed in the USA and Europe, and applied to individuals who sought care in dental schools clinics [2,5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%